CHANGE OF HEMOGLOBIN A1C, FASTING PLASMA GLUCOSE AND HS-CRP LEVELS AFTER ONE VISIT SUBGINGIVAL ULTRASONIC DEBRIDEMENT WITH ADJUNCTIVE MINOCYCLINE GEL IN TYPE II- DIABETES PERIODONTITIS PATIENTS - Yooyen, Jintana; Srisuwantha, Rungtiwa; Nantakeeratipat, Teerachate; Thongsiri, Chuencheewit; Laosrisin, Narongsak (Srinakharinwirot University Journal of Sciences and Technology, 2022)
Objective: To evaluate the level of HbA1c (hemoglobin A1C), FPG (fasting plasma glucose) and hs-CRP (high sensitivity C-reactive protein) changes by the effect of one-visit subgingival ultrasonic debridement with adjunctive minocycline gel in type II diabetes-periodontitis patients. Materials and methods: 60 patients were diagnosed as periodontitis according to 2018 classification with type II diabetes and randomly devided into test or control groups. The test groups were received one-visit subgingival ultrasonic debridement with adjunctive minocycline gel (n=30) at baseline and 3 months while the control groups were received one-visit subgingival ultrasonic debridement only (n=30) at baseline and 3 months. Blood sampling was performed at the baseline, three and six months after treatment. HbA1c, FPG and hs-CRP level were analyzed. Results: 58 patients remained in the final analysis. In subjects with poorly controlled diabetes (HbA1c>8%), HbA1c level in the test groups were significantly decreased compared to the control group after three months of treatment. Moreover, the hs-CRP level in the test groups were significantly decreased compared to the control group after six months of treatment. Conclusions: One-visit subgingival ultrasonic debridement with adjunctive minocycline gel in poorly controlled type II diabetes patients could reduce HbA1c and hs-CRP level more than one-visit subgingival ultrasonic debridement only.